Perencanaan Arsitektur Enterprise Pada Perusahaan Jasa Logistik Menggunakan Kerangka Kerja TOGAF ADM - Pini Singgrit; Tarmuji; Dayat Rohmattulloh; Rahayu Siti Fatimah (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2022)
PT XYZ is a logistics delivery service company. This company has several types of delivery, namely inbond (delivery for within the city), national delivery, and international delivery. In supporting its business processes, PT XYZ has many branches and many shipping vendors spread across the islands in Indonesia. However, the business process is quite complex and has many intersects with other vendors. There are still many work activities that are carried out manually, including printing and pasting airway bill numbers, reporting delivery problems which are done through short message applications, vendor registrations that still use physical correspondence. To overcome the problems that exist at PT XYZ, it is felt that there is a need for an enterprise architecture that can align organizational goals, business processes, existing applications, and the technology used. Therefore, this study aims to design an enterprise architecture using TOGAF (The Open Group Architecture Framework) with the ADM (Architecture Development Method) method through the Preliminary phase, Requirements Management phase, Architecture Vision phase, Business Architecture phase, Information System Architecture phase, and the Technolghy Architecture phase. Later the results of this research will produce a blueprint that can be proposed to be implemented at PT XYZ.